Cavovarus deformity in Charcot-Marie-Tooth disease: is there a hindfoot equinus deformity that needs treatment? - Beckmann, Nicholas A.; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Wallroth, Annika; Müller, Sebastian; Dreher, Thomas (Journal of foot and ankle research, 2015)
Charcot-Marie-Tooth disease (CMT), one of the most common hereditary neurologic disorders, often results in debilitating cavovarus foot deformities. The deformities are still not fully understood, and the treatment recommendations are consequently heterogeneous, often including calf muscle or Achilles tendon lengthening.